The effect of PjBL, PBL, and STEM learning methods on student learning outcomes on photosynthesis material - Silaban, Oky Rizkiana; Surakusumah, Wahyu; Sanjaya, Yayan (Department of Biology Education, Universitas Pendidikan Indonesia, 2024)
Photosynthesis is a vital process in the biological world which is the basis for the survival of plants. It is important to ensure that the learning methods used are able to provide students with a deep understanding and encourage the development of critical and creative thinking skills in accordance with the demands of the independent curriculum. Several methods offer learning approaches that focus on applying theoretical concepts in practical contexts, such as PJBL, PBL, STEM and Conventional methods. It is hoped that this research can contribute to improving the quality of high school biology learning by providing insight into the effectiveness of different learning methods. The research method used is a Quasi Experimental method with a Posttest Only Design type. The research sample was four high school XII science (IPA) classes using purposive sampling. The results of the hypothesis test show that the Sig. less than 0.05, so it rejects Ho and accepts H1, that there are differences in learning outcomes using PJBL, PBL, STEM and conventional methods. Based on the mean rank, it was found that the STEM method was better than the PJBL, PBL and conventional methods.